Interface catalysis by Pt nanocluster@Ni3N for bifunctional hydrogen evolution and oxygen evolution. (15th July 2020) - Pei, Yu; Rezaei, Babak; Zhang, Xuyang; Li, Zichuang; Shen, Hangjia; Yang, Minghui; Wang, Jiacheng
Abstract : Pt@Ni3 N catalysts with plentiful contact between Ni3 N and Pt species were fabricated by a facile strategy. The Pt@Ni3 N with low amount of Pt clusters shows excellent electrocatalytic activity of HER and OER in alkaline media. Abstract : Due to their importance for practical applications in energy conversion, resolving the kinetic issues of water-dissociation in alkaline media for Pt-based electrocatalysts remains an ongoing challenge. Herein, the electronic properties of Pt could be modified with a nickel nitride (Ni3 N) support through forming an interface of a low ratio of Pt nanoclusters (Pt NCs) via a simple impregnation approach combined with nitridation. 1.5Pt@Ni3 N-360 can offer excellent bifunctional performance for both the oxygen evolution reaction (OER) and the hydrogen evolution reaction (HER) which is competitive with commercial IrO2 and Pt/C catalysts under alkaline media. It shows a low overpotential at 10 mA cm −2 (285 and 71 mV) and a small Tafel slope (57 and 48 mV dec −1 ) for OER and HER, respectively. The excellent bifunctional electrochemical activity of 1.5Pt@Ni3 N-360 is due to the interface and synergetic effect between Ni3 N and dispersed Pt clusters, which changes the electron distribution of the material, so that the hydrogen adsorption energy tends to the optimal value (Δ G H* ∼ 0). It is believed that the utilization of low-ratio Pt as an co-electrocatalyst with a variety of metal nitrides opens new horizons and opportunities to fabricate more efficient electrocatalysts for broad applications in energy-related devices.